Hydrophilization treatment of polyimide using Ar-O2 mixture gas surface wave plasma – Oxygen radical density and plasma parameter dependence - Hirukawa, Yoshinari; Ono, Shigeru; Syuichi, Suzuki (International Conference on Plasma Surface Engineering, 2013)
The hydrophilization treatment of polyimide is important in various applications. This paper has described the experimental research findings which explore what the parameter with large effect in the plasma treatment of polyimide is. The low pressure surface wave plasma of the argon oxygen mixed gas which can expect large homogeneity spatially was used for the experiment. The plasma state was measured by the electrostatic probe. The oxygen radical expected to be active species important for surface treatment was measured by the catalyst probe. It turned out that it depends for the water contact angle on the surface of polyimide by which plasma treatment was carried out in an oxygen radical density strongly.